2020
DOI: 10.1097/ta.0000000000002749
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitative endovascular balloon occlusion of the aorta for thoracic trauma: A translational swine study

Abstract: Noncompressible torso hemorrhage in trauma is particularly lethal. Resuscitative endovascular balloon occlusion of the aorta (REBOA) has the potential to stabilize these patients, but currently is contraindicated for major thoracic bleeding. The goal of this study was to evaluate the effect of REBOA on the hemodynamic and metabolic profile as well as its effect on early survival in a porcine model of thoracic hemorrhage and shock. METHODS Forty-eight male Yorkshire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
3
12
0
2
Order By: Relevance
“…There is concern about increasing bleeding due to increased blood pressure. A recent study that included three porcine models of thoracic trauma (lung injury, thoracic venous injury or subclavian artery injury) revealed that the use of REBOA does not aggravate lung damage or increases exsanguination rate 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is concern about increasing bleeding due to increased blood pressure. A recent study that included three porcine models of thoracic trauma (lung injury, thoracic venous injury or subclavian artery injury) revealed that the use of REBOA does not aggravate lung damage or increases exsanguination rate 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Existe preocupación por el incremento de la hemorragia en función del aumento de la presión arterial. Un estudio reciente que incluyó tres modelos porcinos de trauma torácico: lesión del parénquima pulmonar, lesión venosa torácica o lesión de la arteria subclavia reveló que el uso del REBOA no exacerba el daño pulmonar ni incrementa la tasa de exanguinación 38 .…”
Section: Discussionunclassified
“…Furthermore, data from animal models support the use of REBOA in penetrating thoracic trauma (41,42). For example, Glaser et al (42) assessed the hemodynamic response to REBOA in a swine model of hemorrhagic shock and penetrating thoracic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, data from animal models support the use of REBOA in penetrating thoracic trauma (41,42). For example, Glaser et al (42) assessed the hemodynamic response to REBOA in a swine model of hemorrhagic shock and penetrating thoracic injuries. After inflicting pulmonary parenchymal, thoracic venous, and subclavian artery injuries and treating them with and without REBOA, there were no significant differences in the total thoracic blood loss or short term survival between the REBOA and non-REBOA groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation